Cryogel Monoliths for Analyte Enrichment by Capture and Release - Fosso Tene, Patrick L (Langmuir : the ACS journal of surfaces and colloids, 2021)
A platform based on cryogel monoliths in small capillaries, which allows very strong enrichment of an analyte through a capture and release process, is described. For their preparation, a photoreactive copolymer solution containing capture molecules of interest is filled into a capillary, frozen in, and then photochemically transformed into cryogel monoliths through C,H-insertion cross-linking reactions. As a test example, the platform is used for the preconcentration of dopamine from bovine serum albumin and urine samples through capture and release processes. During capture from a large volume and release into a smaller volume, the platform shows recovery rates up to 97% and allows up to a roughly 630-fold enrichment of the concentration of the analyte. The presented platform could be used as a disposable device for the purification and enrichment of a variety of cis-diol-containing samples